RNAi spray-induced gene silencing of EPSPS by topical application of dsRNA in the weed Digitaria insularis - Cintra, Leonardo A.; Da Rosa, Juliana; De Assis, Rafael; Marin, Silvana R. R.; Adegas, Fernando S.; Rech, Elibio L.; Nepomuceno, Alexandre L.; Mertz-Henning, Liliane M. (Frontiers in Plant Science, 2025)
The expanding cultivation of grains to meet agro-industry demands, the implementation of more efficient, sustainable, and integrative management practices capable of mitigating the selection of resistant pests and weeds becomes necessary. Due to the intensive application of chemical herbicides, in addition to environmental impacts, led to the development of resistance mechanisms in weed populations, such as sourgrass (Digitaria insularis). These mechanisms complicate management efforts, escalate production costs, and diminish productivity. In this context, RNA interference (RNAi) technology has emerged as a promising molecular tool for the targeted control of weeds, owing to its specificity in the post-transcriptional silencing of vital genes. This study investigated the application of RNAi technology for the suppression of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) gene expression in D. insularis, a weed species of significant agronomic importance in Latin America. A double-stranded RNA (dsRNA) sequence, specifically designed for the EPSPS gene, was synthesized via bacterial fermentation with a strain of E. coli HT115, extracted using TRIzol™ and purified with phenol: chloroform: isoamyl alcohol, and applied topically in D. insularis leaves. The subsequent phenotypic and molecular effects were evaluated. The spray application of the dsRNA resulted in a 44% reduction in the plant's shoot dry mass and a 75% reduction in the number of tillers, thereby indicating consistent physiological impacts due to gene silencing. Quantitative reverse transcription PCR (qRT-PCR) analysis confirmed a significant suppression of EPSPS transcript levels following treatment, suggesting partial gene silencing. These findings collectively demonstrate the efficacy of RNAi in modulating gene expression in D. insularis, thereby underscoring its potential as a sustainable biotechnological strategy for the development of novel weed control methodologies.